Second republic the government and politics in India - Singh S N (Lucknow New Royal Book, 2004)
The book is an attempt to probe into our polity, its functioning and provide an alternative model which may be more realistic in view of Indian ethos. It is divided into four parts. The first part provides a historical background form of governance in di
Keywords: Government and politics; India